Efficacy and safety of Euiiyin-tang in Korean women with obesity: A randomized, double-blind, placebo-controlled, multicenter trial. (June 2020) - Cheon, Chunhoo; Song, Yun-Kyung; Ko, Seong-Gyu
Highlights: This study was the first clinical trial to evaluate the efficacy and safety of Euiiyin-tang for the treatment of obesity. Administration of Euiiyin-tang had potential weight loss effects in obese women. In a multivariate analysis, only Euiiyin-tang increased the success rate of weight loss. Abstract: Background: Obesity is a global health problem and its incidence is on the rise. Euiiyin-tang is an herbal medicinal formula that is often used in the clinical treatment of obesity. The purpose of the present study was to evaluate the efficacy and safety of Euiiyin-tang in obesity treatment. Methods: A randomized, double-blind, placebo-controlled, multicenter trial was conducted. Participants with obesity were randomly assigned to receive Euiiyin-tang or placebo 3 times daily for 12-weeks. The primary outcome was weight reduction between the baseline and 12 weeks. The secondary outcomes included the rate of weight loss compared to baseline, and changes in body mass index, lipid profiles, and questionnaires related to the quality of life and diet. Safety factors, such as vital signs and laboratory parameters, were also measured. Results: A total of 149 participants were randomly distributed to either the Euiiyin-tang group (n = 76) or the placebo group (n = 73). Weight reduction in the Euiiyin-tang group was significantly greater than that in the placebo group (2.50 kg in the Euiiyin-tang group vs. 0.82 kg in the placebo group). The participant response rates of ≥3% weight loss compared to baseline was 36.8 % in the Euiiyin-tang group and 17.8 % in the placebo group. Body mass index, waist circumference, and hip circumference showed a greater change in the Euiiyin-tang group than in the placebo group (1.00, 3.23, and 2.00 in the Euiiyin-tang group vs. 0.33, 1.96, and 0.86 in the placebo group). Questionnaires, lipid profiles, and safety factors did not show significant differences between groups. Conclusion: The results of this study suggest that Euiiyin-tang has beneficial effects on weight loss. Trial Registration: Clinicaltrials.gov NCT01724099